2010
DOI: 10.1051/0004-6361/201014645
|View full text |Cite
|
Sign up to set email alerts
|

Cold dust clumps in dynamically hot gas

Abstract: Aims. We present clumps of dust emission from Herschel observations of the Large Magellanic Cloud (LMC) and their physical and statistical properties. We catalog cloud features seen in the dust emission from Herschel observations of the LMC, the Magellanic type irregular galaxy closest to the Milky Way, and compare these features with H i catalogs from the ATCA+Parkes H i survey.Methods. Using an automated cloud-finding algorithm, we identify clouds and clumps of dust emission and examine the cumulative mass d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The simulated dust traces the location of the bar; similarly, observed PAHs appear to be enhanced along the LMC stellar bar (Paradis et al 2009;Meixner et al 2010). Kim et al (2010) note that D is relatively uniform across the LMC, except in the vicinity of supershells, which are clustered around the bar (Williams et al 1999). Molecular clouds in the LMC are distinct and well spread throughout the disc (Fukui et al 2008), andKawamura et al (2009) establish the physical association between very young clusters in the LMC and GMCs.…”
Section: Spatial Distributions In the Lmcmentioning
confidence: 66%
“…The simulated dust traces the location of the bar; similarly, observed PAHs appear to be enhanced along the LMC stellar bar (Paradis et al 2009;Meixner et al 2010). Kim et al (2010) note that D is relatively uniform across the LMC, except in the vicinity of supershells, which are clustered around the bar (Williams et al 1999). Molecular clouds in the LMC are distinct and well spread throughout the disc (Fukui et al 2008), andKawamura et al (2009) establish the physical association between very young clusters in the LMC and GMCs.…”
Section: Spatial Distributions In the Lmcmentioning
confidence: 66%
“…It is now possible, with data from IRAS, Spitzer, and Herschel, to constrain the radial distributions of dust and stars within galaxies (Sauvage et al 1990;Zaritsky 1999;Muñoz-Mateos et al 2009;Mattsson & Andersen 2012), and to analyze the spatial distribution of dust, gas, and starlight in the MW (Paradis et al 2012), M31 (Smith et al 2012), M33 (Boquien et al 2011), and M83 (Foyle et al 2012), and other nearby galaxies (Aniano et al 2012;Galametz et al 2012). Others have added optical, Hα, and UV observations to constrain the evolution and environmental dependence of star formation in the LMC and SMC (Bell et al 2002;Harris & Zaritsky 2004Blair et al 2009;Lawton et al 2010), and clustering analyses have demonstrated the hierarchical formation of star clusters and dust clumps (Bonatto & Bica 2010;Kim et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few decades, various methods of calculating SEDs have been reported. The latest SEDs for the LMC were introduced by Israel et al (2010), Kim et al (2010), andMeixner et al (2010). Galliano et al (2011) probed non-standard dust properties and extended submillimeter excess using the HSO observations.…”
Section: Resultsmentioning
confidence: 99%